MENINGKATKAN MOTIVASI DAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA MELALUI ALAT PERAGA MONTESSORI PADA MATA PELAJARAN MATEMATIKA KELAS IV SD ASSISI MEDAN - Patri Janson Silaban (FIP Unimed, 2018)
The purpose of this research is to improve students 'learning motivation through montessori teaching tool, to improve students' mathematical understanding through montessori teaching tools on basic competence of integer counting, to know student response to montessori teaching tool on basic competence of integer counting, and to know the effectiveness of learning through props montessori. Student motivation on learning props on the basic competence of integer mixed count operation with the average class for student learning motivation has increased from 84.77% in cycle I to 87.32% in cycle II. Thus, learning montessori props can improve the motivation of fourth grade students of SD Asisi Medan on the competence of integer mixed count operation. Keywords: Motivation, Montessori, Mathematics